ANALYTICAL STUDY OF THE MOST IMPORTANT SOURCES OF CONTAMINANTS WASTEWATER IN ALEPPO - Jamil Abbass (Mesopotamia Journal of Agriculture)
This Study has been conducted to determine the most crucial of pollution and evaluate the percentage portions of these sources out of the whole sewage water in Aleppo city. the chemical characteristics of raw domestic sewage water and the amount of sewage water that goes in to the total run water in some different areas in Aleppo (low, medium, and high income areas).had been studied.For the( pH, NH4, TDS, BOD5, COD), all values are down allowable concentration based Syrian Standards 2850 for 2002. For the low income areas, an excess of TSS values during morning hours. While an excess of PO4 values and those of olis and lubrication have been noticed during different day hours except for the noon time, and an excess of ABS values at dawn and midnights times. For medium in come areas, there has been an excess in the values of PO4during the different day hours, an excess in the values of oils and lubrications at morning, noon. and night hours. and an excess of ABS values only at midnights. For high in come areas. an excess of TSS values were noticed at noon, an excess of oils and lubrication values at different time except for nights, and an excess of PO4 values at all times and an excess of ABS values at dawn and midnights compared with the allowable concentration based Syrian Standards 2850 for 2002. Based on the initial evaluation, the amount of domestic and industrial sewage water is estimatedat 480000 m3/day. Out of this amount about 455500 m3/day that is 94.9% comes form domestic consumption, and 24500 m3/day (5.1%) is industrial sewage.